2004
DOI: 10.1128/jb.186.22.7659-7669.2004
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Repressor of the Shiga Toxin-Encoding Bacteriophage 933W: DNA Binding, Gene Regulation, and Autocleavage

Abstract: The genes encoding Shiga toxin (stx), the major virulence factor of Shiga toxin-encoding Escherichia coli (STEC) strains, are carried on lambdoid prophages resident in all known STEC strains. The stx genes are expressed only during lytic growth of these temperate bacteriophages. We cloned the gene encoding the repressor of the Shiga toxin-encoding bacteriophage 933W and examined the DNA binding and transcriptional regulatory activities of the overexpressed, purified protein. Typical of nearly all lambdoid phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 49 publications
7
64
1
Order By: Relevance
“…Our experiments also suggest differences in the incorporation of the second phage depending on the CI concentration, but more accurate experiments would be necessary to identify the threshold concentration of CI and/or CI homologues necessary to decide whether the incoming phage will integrate or whether superinfection will occur. These observations are in agreement with other authors who anticipate that 933W prophages would direct the synthesis of a tightly regulated amount of repressor (26). They are also consistent with other authors who suggest that repressor differences may be responsible for the variations in toxin and phage production observed in different lysogens obtained with the same host strain (55).…”
Section: Discussionsupporting
confidence: 93%
“…Our experiments also suggest differences in the incorporation of the second phage depending on the CI concentration, but more accurate experiments would be necessary to identify the threshold concentration of CI and/or CI homologues necessary to decide whether the incoming phage will integrate or whether superinfection will occur. These observations are in agreement with other authors who anticipate that 933W prophages would direct the synthesis of a tightly regulated amount of repressor (26). They are also consistent with other authors who suggest that repressor differences may be responsible for the variations in toxin and phage production observed in different lysogens obtained with the same host strain (55).…”
Section: Discussionsupporting
confidence: 93%
“…Also, we reported earlier that in intact 933W O R , the 933W repressor does not bind its O R 1 and O R 2 sites at an identical concentration (23), suggesting that the 933W repressor is incapable of binding cooperatively to these two adjacent sites. Cooperativity is not essential to the construction a of lysis-lysogeny switch in a lambdoid phage.…”
mentioning
confidence: 78%
“…We and others have reported that unlike all other well-studied bacteriophages, bacteriophage 933W contains only two, not three, repressor binding sites in O L (16,23,36) (Fig. 1).…”
mentioning
confidence: 80%
“…A linker region connects the two structural domains of the repressor. It contains a specific Ala (or Cys, Leu)-Gly cleavage site that is the target of Cterminal-domain-catalysed proteolysis (Koudelka et al, 2004;Little et al, 1980). Analysis of the cI-like repressor from wSa2mw revealed a structural organization dissimilar to that of the classical lambdoid repressors, making it difficult to envisage a RecA-dependent inactivation.…”
Section: Prophage Induction Is Dependent On Recamentioning
confidence: 99%